2016
DOI: 10.1002/2015je004959
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta thickness and structural rim uplift measurements of Martian impact craters: Implications for the rim formation of complex impact craters

Abstract: The elevated rim in simple craters results from the structural uplift of preimpact target rocks and the deposition of a coherent proximal ejecta blanket at the outer edge of the transient cavity. Given the considerable, widening of the transient cavity during crater modification and ejecta thickness distributions, the cause of elevated crater rims in complex craters is less obvious. The thick, proximal ejecta in complex impact craters is deposited well inside the final crater rim and target thickening should r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
9
24
0
Order By: Relevance
“…Figure 7 illustrates that rim height may vary by several hundred meters for craters in the diameter rangẽ 9-17 km diameter. In addition to providing a more accurate measure of d t , we envision that this detailed analysis of the azimuthal variation in rim height might be of particular value, for instance, in assessing the rim topography in relation to the observed structural uplift of the rim (Sturm et al 2016); the same stratigraphic unit might have different elevations relative to the surrounding terrain (i.e., the preimpact surface). Each crater can be seen to have a unique pattern of rim height variations, but the smallest crater (D = 4.0 km) in our CTX sample of five craters in Fig.…”
Section: Analysis and Observationsmentioning
confidence: 99%
“…Figure 7 illustrates that rim height may vary by several hundred meters for craters in the diameter rangẽ 9-17 km diameter. In addition to providing a more accurate measure of d t , we envision that this detailed analysis of the azimuthal variation in rim height might be of particular value, for instance, in assessing the rim topography in relation to the observed structural uplift of the rim (Sturm et al 2016); the same stratigraphic unit might have different elevations relative to the surrounding terrain (i.e., the preimpact surface). Each crater can be seen to have a unique pattern of rim height variations, but the smallest crater (D = 4.0 km) in our CTX sample of five craters in Fig.…”
Section: Analysis and Observationsmentioning
confidence: 99%
“…D) (Sharpton ; Sturm et al. ). The ring at depth −200 m occurred at the albedo transition and it can mark the extent of the breccia lens (cf.…”
Section: The Linné Impact Structurementioning
confidence: 99%
“…Wall slope is directly proportional to crater d/D as also indicated by the scatter plot in Figure . For similar‐sized craters formed by excavation (and no compaction), the rim height should increase with crater depth because an increased amount of ejecta results in larger depths and also larger rim heights (Sharpton, ; Sturm et al, ). However, the overlap in rim heights of our deep and normal‐depth craters can be explained by a modification in the cratering mechanics due to impact into a high porosity target.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies and nuclear explosion experiments have revealed that the raised rim is a consequence of the structural uplift of the target rocks and the thickness of the ejecta blanket formed by the excavated material during the excavation stage (Roddy et al, ; Shoemaker, ; Shoemaker & Chao, ). Recent observational studies on lunar (Sharpton, ) and Martian craters (Sturm et al, ) have inferred structural uplift to be the primary contributor (>80%) of the elevated rim. The third stage, the modification stage, differentiates a simple crater from a complex crater.…”
Section: Introductionmentioning
confidence: 99%